Sustainable Funding Framework for Student-Led Policy Advocacy and Dialogue in Universities - Omodolapo Eunice Ogunsola; Melvin J. Oshomegie; Blessing Olajumoke Farounbi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Student-led policy advocacy and dialogue play a critical role in shaping higher education governance, fostering civic engagement, and influencing policy development. However, the sustainability of such initiatives is often undermined by limited financial resources, fragmented funding mechanisms, and lack of institutional support. This paper proposes a sustainable funding framework for student-led policy advocacy and dialogue in universities. Using a systematic review of over 100 scholarly articles, policy reports, and practitioner studies published between 2000 and 2024, the study identifies funding strategies, stakeholder engagement approaches, and institutional mechanisms that enhance financial sustainability, accountability, and long-term impact. The framework integrates multi-source financing, performance-linked funding, participatory decision-making, and monitoring mechanisms, providing guidance for university administrators, student organizations, and policymakers. Findings indicate that a data-informed, participatory, and diversified funding approach strengthens the capacity of student-led initiatives to sustain impactful advocacy and dialogue.